HPLC METHOD DEVELOPMENT DETERMINATION OF 4-AMINOPHENOL, 2-ASETAMIDOPHENOL, ACETANILIDE, 4-NITROPHENOL, AND 4-CHLOROACETANILIDE IMPURITIES IN PARACETAMOL INJECTION - Gede Widya Sputra, I
Method of analysis impurities determination of paracetamol injection using High Performace Liquid Chromatography (HPLC) has been developed by applying quality risk assesment and Quality by Design concept. Optimum chromatographic condition has been obtained on Ll 1 column (Acquity UPLC BEH Phenyl with dimensions of 2.1x50 mm and 1.7 urn particle size), column temperature maintained at 45 oc, with flow rate of 0.35 mL/min. obile phase consists of pH 6.5 ammonium formate buffer and methanol using ent elution, peak detected using uv detector at 230 nm. Method operational design range has been verified for flow rate in the range of 0.2 mL/min to 0.5 mL/min, buffer pH in the range of 6.0 to 7.0, column temperature in the range of 30 oc to 60 oc. Impurities of 4aminophenol (AF), 2-asetamidophenol (AAF), acetanilide (AA), 4-nitrophenol (NF), and 4-chloroacetanilide (KA), can be well separated with quantitation limit of 0.36 ug/mL, 0.42 ug/mL, 0.29 ug/mL; 0.72 ug/mL, and 0.1 ug/mL respectively. The method has been validated and resulted in valid method in the range of 40% to 160% of working concentration.